What drivers affect entrepreneurial activity in the transition economies? The case of the Visegrad countries - Justyna Zygmunt (Institute of Economic Research (IER), 2017)
While a large literature exists linking entrepreneurship with its drivers in developed economies, entrepreneurship issues in the transition economies are still no entirely recognised. The Visegrad countries represent a unique scope for examining drivers affecting entrepreneurial activity in the transition economies, since they faced similarities at the beginning of the transformation. The findings may be supportive in identifying threats and opportunities of the economic development of Central and Eastern Europe regions.This paper contributes to the literature on entrepreneurship by focusing on drivers of entrepreneurial activity in the transition economies. The aim of the paper is to analyse how entrepreneurial activity in respective Visegrad countries is influenced by various drivers.Entrepreneurship activity and its drivers in the Visegrad countries were considered for the 2004-2014 period. Hypotheses were tested with the usage of an Ordinary Least Squared regression. F-test was employed to test estimated regressions. Goodness-of-fit of the regressions was controlled with the coefficient of determination. To check for the collinearity, Pearson's correlation coefficient was used.In this paper the approach for improving the understanding of issues related to entrepreneurship in the transition economies is made. This paper contributes to the understanding of how entrepreneurship activity in the Visegrad countries is influenced by various drivers. The main finding is that although entrepreneurial activity in the Visegrad countries seems to be influenced by similar drivers that have been identified for developed economies, the way in which respective drivers matters for entrepreneurship is, in certain cases, distinct. The findings may attract attention of policymakers and may be useful in the processes of policy pursuing.
Keywords: L26; P25; R11; 330; entrepreneurship; transition economies; the Visegrad countries